2020
DOI: 10.1111/apt.15692
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: biologics and risk of infection or cancer in elderly patients with inflammatory bowel disease

Abstract: Background: Uncertainty exists concerning the risk of infection and cancer associated with biologic therapies in elderly patients with inflammatory bowel disease (IBD). Aims:To identify, synthesise and critically appraise the available evidence on the topic. Methods:We systematically searched Medline/PubMed, Embase and Scopus, through October 2019, and recent conference proceedings, to identify studies investigating the risk of serious infections, opportunistic infections, any infection and cancer in elderly I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 52 publications
(138 reference statements)
3
43
0
1
Order By: Relevance
“…reported the high expression of ACE2 in enterocytes and the readily infected enterocytes by 2019-nCoV [ 28 ]. However, Lines of evidence suggest the increased risk for 2019-nCoV infection of pregnant and older patients with IBD [ 29 , 30 ], pointing out the putative hazard of ACEIs or ARBs administration. In conclusion, neither ACE2 downregulation nor ACEI is the ideal treatment for COVID-19 patients with gut diseases, and combination therapy of ACEI and calcium blocker merits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…reported the high expression of ACE2 in enterocytes and the readily infected enterocytes by 2019-nCoV [ 28 ]. However, Lines of evidence suggest the increased risk for 2019-nCoV infection of pregnant and older patients with IBD [ 29 , 30 ], pointing out the putative hazard of ACEIs or ARBs administration. In conclusion, neither ACE2 downregulation nor ACEI is the ideal treatment for COVID-19 patients with gut diseases, and combination therapy of ACEI and calcium blocker merits further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Both Piovani et al (RR 2.70, 95% CI 1.56–4.66, serious infections) and Borren and Ananthakrishnan (OR 11.22; 95% CI 3.60–34.99, any infection) found that the risk of infections was substantially increased when comparing older anti-TNF users to older non-users. [ 14 , 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…90 91 Other covid-19 risks situation comprise older patients with IBD with comorbidities as well as patients suffering from malnutrition who may be at risk for infections and severe courses of the disease, respectively. [92][93][94][95] Furthermore, dependent on the local situation, there could be an increased risk for covid-19 in the context of IBD surgery in the hospital. Finally, experimental covid-19 treatment with hydroxychloroquine or remdesivir may increase the risks for drug-drug interactions with established IBD medications ( www.…”
Section: Immunotherapy In Ibd: Potential Effects On Covid-19mentioning
confidence: 99%